HACCP in the meat industry - Brown, Martyn (Woodhead Publishing in food science and technology, 2000)
HACCP is a systematic approach to the identification, evaluation, and control of food safety hazards. It is being applied across the world, with countries such as the US, Australia, New Zealand, and the UK leading the way. However, effective implementation in the meat industry remains difficult and controversial. HACCP in the meat industry provides a survey of principles and practices, providing a guide to making HACCP systems work in the meat industry